Optimization, physical-chemical evaluation and healing activity of chitosan ointment - Dania Pérez; Nilia de la Paz; Mirna Fernández; Niurys Mantilla; Mariela Peña; Addis Menéndez (GarVal Editorial Ltda., 2019)
Context: Chitosan has received attention as a functional, sustainably renewable, nontoxic and biodegradable biopolymer for pharmaceutical applications such as healing agent. Aims: To design a semisolid pharmaceutical form (ointment), employing 1% chitosan as an active pharmaceutical ingredient. Methods: The formulation was carried out through D-optimal mixing design, with a linear model. Variation components evaluated were the concentration of sodium hydroxide, water and anhydrous lanolin. Variables included those of response pH and extensibility. Three batches were produced, and the physical and chemical stability of the ointment was assessed through stress and shelf-life tests for 24 months. Physical-chemical parameters studied included organoleptic characteristics, chitosan content, rheological behavior, apparent viscosity, pH and extensibility. Wound healing activity was also tested for burns damage model in rats. Results: The mixture design showed that the best formulation was the one containing 0.12% sodium hydroxide, 20.0% anhydrous lanolin and 40.0% water, with the mechanical-structural behavior characteristics of a semisolid product. This product had healing effects and showed adequate physical chemical stability during the time under study. Conclusions: The results of this study suggest that 1% chitosan ointment design favors scarring in the second-degree burn damage model in rats skin applied for 14 days at the rate of daily administration.